Funding Self-Employment – The Role of Consumer Credit - Kneiding, Christoph (Taylor and Francis, 2013)
This article investigates whether self-employed households use consumer loans – in particular, instalment loans and overdrafts – to finance business activities. Controlling for financial and nonfinancial household variables, we show that self-employed households particularly use personal overdrafts significantly more often than employee households. When analysing the correlation between consumer loan take-ups and consumption of self-employed in comparison to employee households, we find first evidence that overdrafts are used by self-employed to finance their business as well. This indicates that intermingling constitutes a financing strategy when regular business loans might not be accessible.